2017
DOI: 10.1186/s13063-017-1963-y
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Systematic, Comprehensive, One-to-One Training (SCOOT) program for new scooter users: study protocol for a randomized control trial

Abstract: BackgroundMobility scooters can facilitate community participation among individuals with mobility limitations. However, accidents are a serious concern with scooter use. Scooter training has been recommended to improve safety, but there are currently few validated programs available. Therefore, we developed a Systematic, Comprehensive, One-to-One Training (SCOOT) program for scooter users. We will conduct a study to evaluate the outcomes produced by the provision SCOOT.MethodsThis feasibility study will use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Collisions involved cars, trucks, or buses in 67% of cases ( Figure 4a) and predominantly occurred at junctions or intersections (70%; Figure A1.6d). The findings are (partly) in line with reports from previous studies (Cassell and Clapperton 2006;Gibson et al 2011;LaBan and Nabity 2010;Mortenson et al 2017). Gibson et al (2011) reported that most MMSrelated fatalities were the result of collisions with a motor vehicle, and the most common cause of death was a head injury.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Collisions involved cars, trucks, or buses in 67% of cases ( Figure 4a) and predominantly occurred at junctions or intersections (70%; Figure A1.6d). The findings are (partly) in line with reports from previous studies (Cassell and Clapperton 2006;Gibson et al 2011;LaBan and Nabity 2010;Mortenson et al 2017). Gibson et al (2011) reported that most MMSrelated fatalities were the result of collisions with a motor vehicle, and the most common cause of death was a head injury.…”
Section: Discussionsupporting
confidence: 89%
“…Human factors are important to study because PMD drivers are a multifaceted subgroup of VRUs, which may contribute to an increased complexity in injury prevention strategies. Previous research has highlighted the importance of proper training in managing the PMD (Cassell and Clapperton 2006;Cordes et al 2018;Jancey et al 2013;Jannink et al 2008;Mortenson and Kim 2016;Mortenson et al 2017;Murphy et al 2014;Nitz 2008;Opalek et al 2009;Toosizadeh et al 2014). Because many PMD drivers experience difficulties maintaining an upright seated posture when subjected to external forces, seat belts and leg rests have been strongly recommended (Cooper et al 1998;Corfman et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Seven of the ongoing studies (Dean, 2021;Edgren, 2019;Haeger, 2022;Nct, 2015;Nct, 2020a;Salbach, 2019) are exploring outdoor mobility interventions in older adults. Two studies Nct, 2020) are exploring outdoor mobility interventions after stroke, one in people with Parkinson's Disease (Nct, 2018a), one in mobility scooter users (Mortenson, 2017) and one in a general population of adults living with long-term disabilities (Nct, 2018). The specific type of outdoor mobility interventions could not be described due to limited descriptions in trial registries and protocols of most of the ongoing studies.…”
Section: Ongoing Studiesmentioning
confidence: 99%
“…Occupational therapists could take the initiative to collaborate with other key stakeholders, including mobility scooter users, vendors, and governmental agencies to Currently, studies show that no evidence-based training programme is available [15,39,40]. However, only one study [41] showed that having a full-scale environmental simulation would be beneficial in the identification of usability barriers in the community.…”
Section: Implications For Occupational Therapy Practicementioning
confidence: 99%